Jellyfish galaxies with the IllustrisTNG simulations: supermassive black hole activity in dense environments with ram-pressure stripped satellites - Kurinchi-Vendhan, Shalini; Rohr, Eric; Pillepich, Annalisa; Zinger, Elad; Ayromlou, Mohammadreza; Joshi, Gandhali D. (Monthly notices of the Royal Astronomical Society, 2025)
Jellyfish galaxies are extreme examples of how galaxies can transform due to dense environmental effects. These satellite galaxies suffer from ram-pressure stripping, leading to the formation of their distinctive gaseous tails. Some recent observational studies find that jellyfish galaxies are more likely to host active galactic nuclei (AGN) compared to central galaxies of the same mass, suggesting a link between ram pressure and supermassive black hole (SMBH) accretion. We use the IllustrisTNG cosmological-magnetohydrodynamical simulations, namely TNG50 and TNG100, to explore the presence of AGN in jellyfish galaxies with $M_{\rm {stellar}}\simeq 10^{9.5-10.8}\, \rm {M}_\odot$ at redshift $z=0$ from the Zooniverse ‘Cosmological Jellyfish’ citizen-science project. Compared to central galaxies, jellyfish are more likely to host an AGN ($L_{\rm AGN}\ge 10^{44}\, \mathrm{erg\, s^{-1}}$) particularly at high stellar masses ($M_{\rm stellar}\gtrsim 10^{10}\, \mathrm{M_\odot }$). Jellyfish are also more likely to host an AGN than satellites of the same mass, largely because many satellite galaxies are gas-poor and therefore have lower SMBH accretion rates. Compared to non-jellyfish satellites with similar gas content, jellyfish typically undergo stronger ram pressure and have higher central gas densities along with lower central gas sound speeds, although these effects are smaller at lower stellar masses ($M_{\rm stellar}\lesssim 10^{10}\, \mathrm{M_\odot }$). Together with case studies of individual galaxies, our population analysis indicates that ram pressure can play a key role in fuelling AGN activity in a large fraction of jellyfish, where gas compression can lead to intense episodes of AGN feedback and star formation. Thus, it is essential to consider both environmental and secular processes for a more complete picture of satellite galaxy evolution.
Online verfügbar: 05. August 2025, Artikelversion: 02. September 2025
Gesehen am 29.01.2026